Advanced Integrated Process Modelling of Ni-Cu Sulphide Treatment at the Xstrata Nickel Sudbury Smelter - N. Tripathi; R. Pandher; R. Schonewille (Canadian Institute of Mining, Metallurgy and Petroleum, 2011)
Advanced process modelling tools were developed for the Xstrata Nickel Sudbury Smelter flow sheet using a combination of FACTSAGE TM METSIMTM and ARENATM software. These tools were employed to assist with plant optimisation, emission control, process design, troubleshooting and case studies as applied to the smelter. The development of process modelling tools in pyro-metallurgy commonly involves an in-depth study of the therm o-chemical properties (heat capacity, liquidus temperature, etc.) of all high temperature phases, usually matte and slag. The preferred tool for this purpose is FACTSAGETM, a well-known then-no-chemical modelling software package. The results from the therm o-chemical model have been subsequently incorporated into the development of a process model for the entire smelting facility using the METSIMTM platform. Such process model also includes a number of special features adopted to effectively simulate the complex industrial phases; matte and slag systems. To ensure the robustness and reliability of the process model, several process parameters and assumptions were verified with laboratory and plant data. Consequently, the model includes the ability to examine the impact of a number of plant parameters on potential plant performance. Primary variables are the percent sulphur elimination during concentrate roasting, furnace matte grade and degree of matte metallization. Key output parameters include operating temperature, furnace coke requirement, sulphuric acid production, CO2 emissions and overall energy requirements. Selected outputs from the process model (for example blowing time, slag production rate and matte converting rate) can then be utilised in the development of a discrete event model (DEM) for the smelter using ARENATM software. Incorporation of reliable and validated mass balance parameters enhances the robustness and reliability of the DEM model. The integration of then-no-chemical, process and DEM modeling tools has a distinct advantage in planning plant trials and examining process design initiatives at Xstrata Nickel's Sudbury Smelter. The present paper discusses the development of these three models and the synergies existing among them. Typical results from all three models are also presented.